A critical analysis of human improvement projects from the perspective of the self-organization theory - C. Broens, Mariana (Natureza Humana - Revista Internacional de Filosofia e Psicanálise, 2020)
Based on the theory of self-organization, the objective of this paper is to critically discuss the theses defended by the postulators of two projects that aim to improve human nature: eugenics and transhumanism. We will try to show that the “science of eugenics”, proposed by Francis Galton (1883), and the contemporary transhumanist project, outlined since the second half of the 20th century, share the controversial belief that human beings, through science and technology, are able to successfully control the evolutionary processes of human species. We will try to show that this belief disregards the central characteristics of the complex self-organized adaptive evolutionary processes of organisms in general. For this purpose, we will critically analyse the central theses of the transhumanist project and the “status quo bias” argument proposed by Bolton and Ord (2006) in defence of such theses. We conclude by emphasizing that the proponents of the contemporary transhumanist project would benefit from a fallibilistic perspective that would allow them to face the project’s social and ethical possible implications with epistemic prudence.